Shigemori Mirei : un regard créatif sur l’art des jardins - Murielle Hladik (Projets de Paysage)
As a landscape designer as well as a garden historian, Shigemori Mirei (1896-1975) played a major part in the new creation and reinvention of the Japanese gardens design, at the dawn of the twentieth century. Shigemori supervised an extensive survey throughout the whole Japanese archipelago at a time during which some of these gardens were falling into disrepair, or even disappear, whereas they are now considered as "National Treasures". These surveys, and especially the huge work of restoration and creation of new gardens conducted by Shigemori, greatly contributed to the enhancement and renewal of this very fragile and ephemeral heritage of garden design. Furthermore, in parallel with the development of this gigantic encyclopaedia focused on gardens, Shigemori Mirei has also been a famous garden designer whose work relies on a deep knowledge of the past to achieve a highly innovative creation.